New Developments in Eco-Innovation Research (Sustainability and Innovation,, 2018)
Eco-innovations are crucial for reducing the environmental damages arising from economic activities, and are one of the main drivers of a successful transition towards sustainable development and remedying essential climate change problems. This book provides an overview of recent advances in the rapidly growing field of eco-innovation research, adopts an interdisciplinary perspective and outlines the main future developmental trends. A broad range of topics are addressed, including a bibliometric analysis of eco-innovation research, the relationship between eco-innovation and corporate sustainability, eco-innovation system analysis, new evidence on the economic effects of eco-innovation, and the relevance of policy and policy mixes for eco-innovation activities. The book is dedicated to Klaus Rennings, one of the most important representatives of this field, who unexpectedly passed away in September 2015.